F Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Cempaka Banjarmasin - Rahmina, Anita; Megawati, Megawati; Dewi, Vonny Khresna; Kirana, Rita (LPPM Universitas Sari Mulia, 2025)
Background : Pregnant women who suffer from anemia can experience negative impacts on themselves and their fetuses, such as fatigue, fetal anemia, low birth weight, premature birth, increased risk of postpartum hemorrhage, intrauterine growth retardation, perinatal death, stillbirth, low tolerance to infection, shortness of breath, and decreased physical and mental performance. Objective : To determine the factors associated with the incidence of anemia in pregnant women in the work area of ​​the Cempaka Banjarmasin Health Center Method : Quantitative non-experimental correlative research design with a cross-sectional approach. The sample in this study was 48 respondents taken using the Accidental sampling technique. The dependent variable is anemia in pregnant women and the independent variables are age, parity and knowledge. The statistical test used chi-square with a confidence level of 95% or (α = 0.05). Results : The results of the study showed that there was a relationship between all variables and anemia in pregnant women. Of all respondents, 10 (20.8%) respondents experienced anemia and 38 (79.2%) respondents did not experience anemia. There is a relationship between age (ρ-value: 0.002), parity (ρ-value: 0.003), and knowledge (ρ-value: 0.009) with the incidence of anemia in pregnant women. Conclusion : The incidence of anemia in pregnant women is influenced by age, parity and knowledge factors in the Cempaka Health Center Work Area.